THE EFFECT OF INVESTMENT DECISIONS AND DIVIDEND POLICIES ON COMPANY VALUE - Selfiani Selfiani; Hendi Prihanto; Usmar Usmar; Wizanasari Wizanasari (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This study aims to see the influence of investment decisions measured by Price Earning Ratio (PER) and dividend policy measured by Dividend Payout Ratio (DPR) on company value measured by Price Book Value (PBV). The sample of this study consisted of 11 companies included in the LQ-45 group listed on the Indonesia Stock Exchange (IDX). This study uses classical assumption tests (nomality test, multicollinearity test, heteroscedasticity test, autocorrelation test) and hypothesis with multiple linear regression test which shows that all variables used have been free of multicollinearity, heteroscedasticity, autocorrelation and all these variables are normally distributed. In addition, this study used SPSS version 21.00. The results of this study show that partially investment decisions have a significant effect on company value and dividend policy does not have a significant effect on company value. However, simultaneously all independent variables in this study have a significant effect on the value of the company.